PENGARUH PUTARAN DAN JARAK LANGKAHPENEKANAN TERHADAP KAPASITASPRODUKSI MESIN PRES BATAKO - ., Muhyin; Setyiawan, Didik (MEKANIKA: Jurnal Teknik Mesin, 2015)
Adobe as a building material to build a house, have a sizeable market. One village Nogosari,Kec.ngadirojo, Kab. Pacitan, from the results of field surveys in the brick-making process is still very less effective,so as to enhance the economy of citizens who are farmers rainfed and productive time work only 4 months.Dihasilkanpun brick production capacity is small enough that 300 pieces / 8 hours. To increase the capacity it needsto be developed and applied the appropriate technology, so the idea the author to replace conventional productiontools are still with vibro brick pressing machine that uses a gasoline engine propulsion. In this case the authorsanalyze lap and suppressive measures the distance to the wall in the mold, which aims to increase productioncapacity and get the best quality.In this study analyzed the round and suppressive measures the distance to the wall in the mold of the productioncapacity in a pressing machine combining brick with round and suppressive measures the distance to the wall in amold with different variables and testing each - each 3 times. Wherein rotation of analysis and distancedivariabelkan as follows rotation 5000 rpm, 4600 rpm, 4000 rpm and a distance of 30 mm, 25 mm, 20 mm. Analysisof the data and the results of the testing showed that the best maximum capacity of 240 units / h at 5000 rpmrotation and a distance of 30 mmKeywords ; brick, vibro (vibration), press (emphasis), capacity.